STUDI ETNOBOTANI TUMBUHAN PADA UPACARA ADAT KEMATIAN DI NAGARI CUBADAK, KECAMATAN DUA KOTO, PASAMAN - Afwina, Tiara Lingga; Fitri, Rahmadhani (Universitas Cokroaminoto Palopo, 2024)
Ethnobotany is a science that studies the reciprocal relationship between people's cultures and plants. One of the examples of ethnobotany can be seen in traditional death ceremonies. The traditional death ceremony is one of the traditional ceremonies carried out by the people of Nagari Cubadak, Dua Koto District, Pasaman. This research aims to determine the plants used in traditional death ceremonies, the parts of the plants used, and their meaning in the use of plants. The method used was by conducting interviews with the community in Nagari Cubadak, Dua Koto District, Pasaman. From the research results, there are 6 plant species belonging to 6 families that are used in traditional death ceremonies.